Damage model of turbine rotor based on DPLS - Chao Dong; Wei Qin; Yongjian Sun (Annals of Systems Biology - Peertechz Publications, 2021)
In today's society, the development of electric power industry is one of the important conditions for the economic construction of a country. Therefore, it is of great theoretical signiﬁcance and value to carry out the research on the damage assessment of turbine rotor. The damage of the turbine rotor is directly related to the process quality, material performance, operation conditions of the equipment itself, and also closely related to the performance of the controller. According to the existing data and starting conditions, a dynamic partial least square prediction model is established and analyzed in this paper, so as to effectively evaluate the stress and damage of the turbine rotor. Before the establishment of dynamic partial least squares model, people study the change law of stress value and damage value mainly through complex mathematical formulas and inconvenient finite element analysis software. After the establishment of dynamic partial least squares model, the staff only need to input the input data (speed, temperature, back pressure) to the model to get the stress. The function is also realized in this paper.